Goldenhar Syndrome and full inclusion - Claus Dieter Stobäus; Carla Rejane Crixel Fernandes (Universidade Federal de Santa Maria (UFSM), 2014)
We discuss the information included in Fernandes' Monograph and opinions of his advisor (Stobäus), centered in interfaces with Special Education/Full Inclusion, pointing anatomic-functional elements of this Syndrome, reviewing difficulties encountered in full inclusion, by an interview with his mother and teacher.